Thickness of Tidemark in Enthesis Fibrocartilage at Distal Epiphyseal Attachment of Quadriceps Tendon and Semimembranosus Tendon - Tahzeeb-Ul- Hassan (Journal of Rawalpindi Medical College, 2015)
ackground: To compare width of zone of tidemark at distal attachment of quadriceps tendon and semimembranosus tendon by routine histology in view of their role as mechanical barrier and site for osteoarthritic live degenerative changes. Methods: The specimens of right sided distal attachment of quadriceps tendon on patella and semimembranosus tendon on tibia were collected from 20 male cadavers of adult age not beyond 40 years from autopsy room, within 24 hours of death. After fixation, dehydration and processing 5um serial sections were cut at 500um interval along the long axis of the tendons. The varying thickness of tidemark were calculated. Results: There were four zones at the attachment sites. These included (1) tendon (2) uncalcified fibrocartilage, (3) calcified fibrocartilage, (4) bone. The zone of uncalcified fibrocartilage was separated from calcified fibrocartilage by calcification front called tidemark. There were marked differences in width of zone of tidemark between quadriceps tendon and semimembranosus tendon insertion. Conclusion: The thickness of zone of tidemark is greater in semimembranosus tendon than quadriceps tendon. As quadriceps tendon is strong extensor with greater mobility and exert more force than semimembranosus which is one of weak flexor of knee joint, so width tidemark is more in semimembronosus tendon than quadriceps tendon.